Effect of vitamin E on trace element levels in various tissues of diabetic rats - Ulas, Mustafa (Dustri-Verlag Dr Karl Feistle, 2012)
We investigated the effect of vitamin E on trace element levels in various tissues of diabetic rats. 30 rats were equally divided into three groups: Group I, control. Group II, diabetic rats; Group III, (diabetic + vitamin E) rats; the group received 100 mg kg(-1) intraperitoneal dose of vitamin E per day after diabetes. At the end of the 30-day experiment, the rats were sacrificed and their tissues were collected for the measurement of zinc, copper, iron, phosphorus, selenium, magnesium, calcium, chromium and manganese. Kidney tissue zinc, copper, phosphorus, selenium and magnesium concentrations in the diabetic group were lower than control group but chromium and calcium were higher. However, kidney copper, iron and phosphorus concentrations in the diabetes + vitamin E group were lower but selenium and chromium were higher. Pancreas tissue zinc and selenium concentrations in the diabetic group were lower than control group but iron, chromium, magnesium and manganese were higher. Meanwhile, pancreas iron and manganese concentrations in the diabetes + vitamin E group were found lower but zinc, selenium and chromium were higher. Liver tissue zinc, copper and selenium concentrations in the diabetic group were lower than control group but chromium and calcium were higher. Liver calcium, phosphorus, and manganese concentrations in the diabetes + vitamin E group were lower but selenium and chromium were higher. Brain tissue selenium concentrations in the diabetic group were lower than control group but iron, chromium and calcium were higher. However, brain zinc, selenium, calcium and chromium concentrations in the diabetes + vitamin E group were higher. Muscle tissue chromium and calcium concentrations in the diabetic group were lower than control group. Moreover, calcium, zinc and magnesium concentrations in the diabetes + vitamin E group were lower but selenium and chromium were higher. Heart tissue copper and selenium concentrations in the diabetic group were lower than control group. Furthermore, phosphorus concentrations in the diabetes + vitamin E group were lower but selenium, magnesium, zinc and iron were higher. Lung tissue magnesium concentrations in the diabetic group were lower than control group but tissue calcium concentrations in the diabetic group were higher than control group. Finally, lung copper, iron, selenium and phosphorus concentrations in the diabetes + vitamin E group were higher. These results indicate that administered vitamin E has significant protective effects on trace element levels of various diabetic tissues.
Keywords: diabetes; vitamin E; zinc; iron; copper; selenium